The effect of allergy and asthma as a comorbidity on the susceptibility and outcomes of COVID-19 - Gao, Ya-Dong; Agache, Ioana; Akdis, Mübeccel; Nadeau, Kari; Klimek, Ludger; Jutel, Marek; Akdis, Cezmi A (International immunology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic causes an overwhelming number of hospitalization and deaths with a significant socioeconomic impact. The vast majority of studies indicate that asthma and allergic diseases do not represent a risk factor for COVID-19 susceptibility nor cause a more severe course of disease. This raises the opportunity to investigate the underlying mechanisms of the interaction between an allergic background and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The majority of patients with asthma, atopic dermatitis, allergic rhinitis, chronic rhinosinusitis, food allergies and drug allergies exhibit an over-expression of type 2 immune and inflammatory pathways with the contribution of epithelial cells, innate lymphoid cells, dendritic cells, T cells, eosinophils, mast cells, basophils, and the type 2 cytokines interleukin (IL)-4, IL-5, IL-9, IL-13, and IL-31. The potential impact of type 2 inflammation-related allergic diseases on susceptibility to COVID-19 and severity of its course have been reported. In this review, the prevalence of asthma and other common allergic diseases in COVID-19 patients is addressed. Moreover, the impact of allergic and non-allergic asthma with different severity and control status, currently available asthma treatments such as inhaled and oral corticosteroids, short- and long-acting β2 agonists, leukotriene receptor antagonists and biologicals on the outcome of COVID-19 patients is reviewed. In addition, possible protective mechanisms of asthma and type 2 inflammation on COVID-19 infection, such as the expression of SARS-CoV-2 entry receptors, antiviral activity of eosinophils and cross-reactive T-cell epitopes, are discussed. Potential interactions of other allergic diseases with COVID-19 are postulated, including recommendations for their management.